2004
DOI: 10.3748/wjg.v10.i3.455
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics inhibit TNF-α-induced interleukin-8 secretion of HT29 cells

Abstract: AIM:To study the effect of probiotics on interleukin-8 secretion in intestinal epithelia when stimulated by proinflammatory cytokines. METHODS:Colonic adenocarcinoma HT29 cells were cultured and divided into four groups: control, TNF-α (group T in short), bifidobacterium (group B), lactobacillus (group L). B. Longum and L. bulgaricus were suspended in culture medium with a concentration of 1×10 8 cfu/ml and added into 24 wells respectively. One hour later TNF-α (10 ng/ml) was added into each well of groups T, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 20 publications
7
46
0
1
Order By: Relevance
“…It has been shown previously that probiotic DNA inhibits IL-8 secretion by HT-29 cells to pathogenic bacterial DNA in a competitive manner (21). Next, probiotics also have been shown to inhibit NF-B in colonic epithelial cells and to suppress IL-8 secretion in intestinal epithelia (3,30). The current data indicate that, next to potential competition with bacterial DNA, probiotic DNA induces tolerance to a subsequent trigger with another TLR ligand dose dependently.…”
Section: Discussionsupporting
confidence: 60%
“…It has been shown previously that probiotic DNA inhibits IL-8 secretion by HT-29 cells to pathogenic bacterial DNA in a competitive manner (21). Next, probiotics also have been shown to inhibit NF-B in colonic epithelial cells and to suppress IL-8 secretion in intestinal epithelia (3,30). The current data indicate that, next to potential competition with bacterial DNA, probiotic DNA induces tolerance to a subsequent trigger with another TLR ligand dose dependently.…”
Section: Discussionsupporting
confidence: 60%
“…In our study, L. plantarum inhibited TNF-a-induced ERK activation, suggesting that L. plantarum may inhibit IL-8 secretion, at least partially, through the ERK pathway. NF-κB regulates IL-8 transcription, and some lactobacilli have been shown to inhibit TNF-a-induced NF-κB translocation to the nucleus and IκB-a degradation [13,14] . We also showed that L. plantarum inhibited the degradation response of IκB-a to TNF-a.…”
Section: Ma Et Almentioning
confidence: 99%
“…Secretion of IL-8 by epithelial cells has been suggested to be important in the pathogenesis of inflammatory bowel diseases, because IL-8 induces migration of inflammatory cells into the mucosa. Some lactobacilli inhibit the induction of IL-8 production by TNF-a in human intestinal epithelial cells [13][14][15] . TNFa-stimulated IL-8 secretion by intestinal epithelial cells is mediated by extracellular signal-regulated kinase (ERK) and nuclear factor κB (NF-κB) [16] .…”
Section: Introductionmentioning
confidence: 99%
“…В конце периода наблюдения в группе, получавшей Bifidobacterium lactis BВ12, индекс SCORAD [первоначально равный 16 (7-25)] составил 0 (0-3,8), тогда как в группе, получавшей Lactobacillus GG, эта вели-чина равнялась 1 (0,1-8,7). Среди детей, получавших смесь без введения пробиотиков, индекс SCORAD соста-вил 13,4 (4,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)2). Таким образом, в данном исследо-вании показана не только эффективность пробиотиков для профилактики аллергии, но и более выраженное действие штамма Bifidobacterium lactis BВ12.…”
Section: обзор литературыunclassified